REFLECTION OF TERMS IN THE HUMAN MIND UNDER THE INFLUENCE OF VARIOUS FACTORS (Conferencea, 2023)
The article sports terminology of using historical terms in the literary text. It is scientifically based that the study of historical terms in the text is an important factor in the manifestation of their poetic and aesthetic value.